Traços funcionais podem explicar uma maior vulnerabilidade de mamíferos à atropelamentos? - Sá, Nayara Luana Rodrigues de Lima (Universidade Federal Rural do Semi-Árido, 2018)
One of the groups most affected by the alteration of the landscape is the mammals because, besides presenting a fragility to the environmental impacts, many of its species are dependent on continuous areas of natural habitat. In this way, the roads can act as a barrier to their displacements. The objective of this study was to verify if functional traits could be influencing the vulnerability of mammals to trampling on roads located around a conservation unit, Seridó Ecological Station, in Rio Grande do Norte. For that, data were collected from October 2014 to October 2016. The mortality rate in the selected sections was calculated using a simple mathematical model of division, then this result was used as a dependent variable and functional characteristics of the species of (day, night, arrhythmic), social behavior (solitary or group), trophic guild (carnivores, insectivores, frugivores, omnivores, herbivores) (forage), forage substrate (terrestrial, terrestrial-arboreal), longevity (years), food independence (weeks), obtained through the specialized literature. was the type of foraging substrate, where the species that have habit of foraging terrestrial were the ma are run over
Keywords: Ecologia de Estradas; Mamíferos; Semiárido; Ecology of Roads; Mammals; Semi-arid; CIENCIAS AGRARIAS::MEDICINA VETERINARIA